Free Vibration of The System of Two Strings Coupled by a Viscoelastic Interlayer - Cabańska-Płaczkiewicz, K. (Engineering Transactions, 2015)
This paper introduces an analytical method of solving the free vibration problem for a continuous system of two strings coupled by a viscoelastic interlayer. The phenomenon of free vibration has been described using a homogenous system of conjugate partial differential equations. After separation of variables in the system of differential equations, the boundary problem has been solved and two complex sequences have been obtained: the sequence of frequency, and the sequence of modes of free vibration. Then, the property of orthogonality of complex modes of free vibration has been demonstrated. Based on complex eigenfunctions, the polyharmonic free vibration has been expanded into the complex Fourier series, coefficients of which have been determined for arbitrarily assumed initial conditions.